GAYA BELAJAR SISWA KELAS XII PADA MATA PELAJARAN PAI MASA PANDEMI DI SMA BRAWIJAYA SMART SCHOOL MALANG - Silvynia Efrida; Ahmad Subekti; Bahroin Budiya (VICRATINA, 2022)
Learning style is very influential on the achievement of knowledge gained by students. The role of a teacher is very important, which must have various ideas to achieve learning objectives in accordance with the previous lesson plan (RPP). Learning styles that have been conveyed to students, and with various learning styles an educator will find it easier to convey the material he teaches to students, then these students can understand or absorb the material taught by the teacher. One of the teacher's strategies in implementing Islamic Religious Education learning with different student learning styles is to use appropriate methods, media and learning models according to the types of learning styles used by students. The location of this research is in SMA Brawijaya Smart School Malang. This study uses a qualitative method in which data collection using the method of observation, interview and documentation as well as supported by an opinion from the experts. The Learning Styles of Class XII Students in PAI Learning in this Pandemic Period are different, but the majority of students type their learning styles using visual (vision) and auditory (hearing) methods which are carried out using an online learning system.